2006
DOI: 10.1519/r-16354.1
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Body Segment Length and Vertical Jump Displacement in Recreational Athletes

Abstract: The purpose of this study was to determine if segmental skeletal length contributes to vertical jump (VJ) displacement in recreational athletes. Skeletal length measurements of the trunk, femur, tibia, and foot were obtained by palpation of bony landmarks and a standard tape measure. A pilot study (n = 10) examined the intratester and intertester reliability for each skeletal measure. The pilot investigation revealed fair to excellent intratester and intertester reliability. Seventy-eight recreational athletes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 0 publications
2
9
0
Order By: Relevance
“…The skelic index (100 × lower limb height/sitting height) is higher in black subjects compared with white subjects of the same age (Meredith & Spurgeon, ; Abe et al., ; Wagner & Heyward, ; Rahmani et al., ). However, skeletal length measurements (trunk, femur, tibia, and foot) in recreational athletes (Davis et al., ) showed that none of the skeletal length was predictive of vertical jump performance with the exception of the small contribution of foot length in men ( r 2 = 0.08, P < 0.033). In the present study, body mass and body height were not significantly different in groups WA and C, but the skelic index was not measured.…”
Section: Discussionmentioning
confidence: 99%
“…The skelic index (100 × lower limb height/sitting height) is higher in black subjects compared with white subjects of the same age (Meredith & Spurgeon, ; Abe et al., ; Wagner & Heyward, ; Rahmani et al., ). However, skeletal length measurements (trunk, femur, tibia, and foot) in recreational athletes (Davis et al., ) showed that none of the skeletal length was predictive of vertical jump performance with the exception of the small contribution of foot length in men ( r 2 = 0.08, P < 0.033). In the present study, body mass and body height were not significantly different in groups WA and C, but the skelic index was not measured.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have investigated variables that can predict vertical displacement (8,(12)(13)(14)19,20), used vertical jump as an independent variable (2,3,5,7,14,18), or tested training methods that can possibly improve vertical jump performance (6,9,11). Consequently, comparison between different populations or training methods should be relatively straightforward.…”
Section: Discussionmentioning
confidence: 99%
“…Looking at the more distal foot measures, which was the main interest of this study, we found no relationship between these measures and jump height specifically for our male subjects. One previous study considered foot length and found that larger feet was related to better jump performance in men only; however, they did not look at other foot measures (9). Previous work investigating relationships between a single-joint ankle jump and anthropometric measures have found contrasting results.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is work that disagrees with these general statements relating anthropometry and performance (1,2). For example, 2 separate studies by Davis et al (9,10) did not find specific relationships between stature or lower leg length and jump performance in groups of recreational athletes. The possibility that differences in results could be due to different populations, elite athletes (1,2) versus recreation athletes (9,10), used in these studies, should be considered.…”
Section: Introductionmentioning
confidence: 98%